Comparing Virtual Reality Tourism to Real-Life Experience: Effects of Presence and Engagement on Attitude and Enjoyment. Issue 5 (20th October 2018) - Wagler, Adam; Hanus, Michael D.
Abstract : With the advent of 360-degree video technology, Virtual reality (VR) headsets can take users to locations in the real world. Despite the increasing number of virtual tourism opportunities using digital VR technology, little research has assessed the effective realism of 360-degree video tourism. This study took users on a guided audio tour of a state Capitol building. Users either took the tour via two-dimensional (2-D) video, immersive 360-degree video using a VR headset, or physically went to the location and walked around the grounds. Users were measured on spatial presence, emotional engagement with the tour, sponsor liking, and tour outreach intentions. Results indicate that users in the two-dimensional viewing condition scored low on all measures relative to the other conditions but that individuals in the physically present and 360-degree video condition had no differences between them. This suggests that 360-degree video tourism may be a strong analogue to a real-world experience.